Adjuvant zoledronic acid and letrozole plus ovarian function suppression in premenopausal breast cancer: HOBOE phase 3 randomised trial. (September 2019) - Perrone, Francesco; De Laurentiis, Michelino; De Placido, Sabino; Orditura, Michele; Cinieri, Saverio; Riccardi, Ferdinando; Ribecco, Angela Stefania; Putzu, Carlo; Del Mastro, Lucia; Rossi, Emanuela; Tinessa, Vincenza; Mosconi, Anna Maria; et al.
Abstract: Aim: The aim of the study is to analyse whether letrozole (L) and zoledronic acid plus L (ZL) are more effective than tamoxifen (T) as adjuvant endocrine treatment of premenopausal patients with breast cancer with hormone receptor–positive (HR+) tumours. Patients and methods: In a phase 3 trial, 1065 premenopausal patients with HR + early breast cancer received triptorelin to suppress ovarian function and were randomly assigned (1:1:1) to adjuvant T, L or ZL for 5 years. Cancer recurrence, second breast or non-breast cancer and death were considered events for the intention-to-treat disease-free survival (DFS) analysis. Results: With a 64-month median follow-up and 134 reported events, the disease-free rate at 5 years was 85.4%, 93.2% and 93.3% with T, L and ZL, respectively (overall P = 0.008). The hazard ratio for a DFS event was 0.52 (95% confidence interval [CI], 0.34 to 0.80; P = 0.003) with ZL vs T, 0.72 (95% CI, 0.48 to 1.07; P = 0.06) with L vs T and 0.70 (95% CI, 0.44 to 1.12; P = 0.22) with ZL vs L. With 36 deaths, there was no significant difference in overall survival ( P = 0.14). Treatment was stopped for toxicity or refusal in 7.3%, 7.3% and 16.6% patients, and in the safety population, grade 3–4 side-effects were reported in 4.2%, 6.9% and 9.1% patients treated with T, L or ZL, respectively. Conclusion: HOBOE study shows that in premenopausal patients with early breast cancer undergoing ovarian function suppression with triptorelin, ZL significantly improves DFS, while worsening compliance and toxicity, as compared with T. (NCT00412022 ) Highlights: In a 3-arm study, we tested zoledronic acid (ZL) vs letrozole (L) vs tamoxifen in patients receiving triptorelin. ZL was significantly better than tamoxifen and not significantly better than L. As expected, compliance and side-effects were worse with ZL.